To Obtain a Patent Non-Infringement Opinion, Or Not to Obtain It. That is the Question! - Ping-Hsun, Chen (Iuris Dictio, 2017)
This paper aims at analyzing the risk of whether to acquire a patent non-infringement opinion. After Seagate, there have been many decisions of either district courts or Federal Circuit involving willful infringement. This paper discusses some observations from those decisions. The observations give a basis for thinking of whether to acquire a patent non-infringement opinion. The analysis is presented in view of a potential or accused infringer, Company T. Company T could be accused of direct or indirect infringement. By discussing either Federal Circuit"™s or district courts"™ cases after Seagate, this paper suggests that though there is no duty to get a patent non-infringement opinion, the best strategy for an accused infringer would still be to have such opinion letter.
Keywords: Willful Infringement; Patent; Non-Infringement Opinion